The Innovation of Learning Mathematics on Introduction of Number for Pre-School Students - Hawa Liberna; Yoga Budi Bhakti; Irnin Agustina Dwi Astuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
The use of technology in learning is very important according to the development of the times. However, the application of technology as a learning medium is still limited. The purpose of this research is to develop interactive multimedia mathematics to improve the learning motivation of early childhood. This research is conducted using a ADDIE model, which consists of four stages: analyze, designing, developing, implementation, and evaluation. Instrument of tis reserach is validation sheets and respons questionnaires. Expert validation is used to validate media consisting of media validation, material validation, and language validation, while student response questionnaires determine practicality. Average validation results from material experts of 3.4, media experts of 3.2, and language expert of 3.3. So that if averaged all, then the validation of mathematics learning media is 3.3 with good categories. Moreover, the practicality of media also shows that it can be easily applied. The observation data also support the effectiveness of the media during the implementation. The result shows that the media confirmed to be effective as it can improve the students' learning motivation.